PENGARUH JENIS SETEK DAN MEDIA PEMBIBITAN TERHADAP PERTUMBUHAN BIBIT TANAMAN LADA (Piper nigrum L.) - , Hariyadi; I. Darmawan; R. Zaubin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1996)
The experiment was carried out at green house of Medicinal and Spice Plant Research Agency, Bogor from May to October 1993. The split plot design in randomized block design was applied for 2 factors and 3 replication. The main plot was 2 kind of bud (secondary branch bud and tertiary branch bud), and the sub plot was 5 different growth media consisted of sand + cow dung + top soil mixed i.e. 1 : 1 : 0 : 1 : 1 : 1 : 1 : 1 : 2 : 1 : 1 : 3 and 1 : 1 4.The kind of bud did not significantly influence the pepper seedling growth. The best seedling shoot growth was obtained by the combination treatments of sand + cow dung + top soil (1 : 1 : 0), and the best seedling root growth was obtained by the combination of sand + cow dung + top soil (1 : 1 : 2